ROLE MODEL AND CAREER PROFILE FOR CAREER DEVELOPMENT OF THE POORIN PHILIPPINE (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2019)
Reduction of the poverty is one of the SDGs and one of the major issues in the developing countries where the poor accounts for larger part of the population. Despite long-term and energetic effort of supporting institution (SI) including NGOs, most of the middleclass poor who occupy the major part of the poor are still staying in poverty. For the fundamental solution, the individual efforts of self-reliant and endogenous development for their independence are indispensable, by those marginalized people themselves who cannot access enough supports of SI.For those who need to become independent, they need to recognize who they are, where they are from (past history) and where they would like to go (goal of their life). However, for their self-independent, motivation for independent and self-development of their own career seem to be useful. Such motivation and career development have close relationship with maturity and self-determination, self-efficacy and personal-causation of the said person, and kind of motivation. Namely, person who has high maturity has high self-determination, hi self-efficacy, hi-personal-causation, and intrinsic motivations are effective, and who has low maturity has low self-determination, low self-efficacy, low personal-causation and extrinsic motivations are effective.In this paper, we proposed a method of ‘role model’ and ‘career profile’ for self-independence through the literature reviews and discussions. Firstly, we present macro vs micro approach of solving poverty issue, then focus on micro approach –we review about motivation, time-perspectives,and career development. Secondly, on role models, we discuss about its definition and functions, role models and mentor, four types of role models. Thirdly, on career profile, we discuss about its definition and functions, self-analysis, structure and elements, life history analysis, and goal setting and roadmap. Finally, we show result of our preliminary questionnaire and discuss about problems and future issues.